INSTITUTIONAL SYNERGY IN SUSTAINABLE PEATLAND MANAGEMENT - Zulkarnaini Zulkarnaini; Sujianto Sujianto; Wawan Wawan; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The main highlight in peatland resource management to date has been the weak institutional synergy directly related to peatland management. This study aims to analyze institutional synergy in sustainable peatland management in the Giam Siak Kecil-Bukit Batu (GSK-BB) Landscape area of Bengkalis Regency. The research design used a mixed approach by combining quantitative and qualitative methods to determine the sustainability of institutional dimensions in peatland management. RAPPEAT analysis was used to analyze the sustainability index of institutional aspects. The results showed that the index and sustainability status of the institutional dimension of peatland management were categorized as less sustainable. Based on the MDS analysis, the institutional dimension only has an index of 49.8%. This result directly illustrates that peatland management in this landscape is not yet oriented towards the institutional dimension.